URGENCY OF UNDERSTANDING MULTIPLE INTELLIGENCES - Yahya, Rosnida (JELIM : Journal of Education, Language, Social and Management, 2023)
Globalization is currently developing very rapidly and is extraordinary. Changes occur in all aspects of life, especially in the field of education. The sophistication of technology makes various information so easily available. This certainly affects the paradigm in the world of education. Student needs or learning objectives slowly change following the times. But unfortunately, currently there are still a lot of educators who have not changed their mindset towards the intelligence of students. There are still many educators who think that smart/intelligent children are children who have high scores in all subjects, especially mathematics and science. Whereas the purpose of learning is that each student is able to overcome their respective problems, of course where the capacity or problems faced by each child will be different. Students are social beings, who will later interact in the community. In community groups, of course, everyone plays their respective roles according to their fields and abilities. Therefore it is time for educators to change their paradigm about student intelligence, towards or oriented to multiple intelligences (multiple intelligences ).